1992
DOI: 10.1136/hrt.67.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Early and late arrhythmias after the Fontan operation: predisposing factors and clinical consequences.

Abstract: Objective-To study the incidence, predisposing factors, and clinical significance of arrhythmias early and late after the Fontan operation for congenital heart disease.Patients and methods-All 104 consecutive patients undergoing Fontan repair from 1975 to 1988 were studied retrospectively. Hospital records were reviewed for perioperative arrhythmia. Clinical information and annual electrocardiograms were available for all 78 hospital survivors during a follow up of up to 13 years (mean 3'7 years).Ambulatory el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(70 citation statements)
references
References 17 publications
3
63
1
3
Order By: Relevance
“…Because of the heterogeneity of cardiac anatomy, we used a qualitative, subjective assessment of systemic ventricular function from multiview 2-dimensional echocardiography, grading it as normal or mildly, moderately, or severely impaired, 20 while accounting for significant AV valve regurgitation by similarly grading the systemic ventricular end-systolic diameter. Right atrial (RA) and LA length and width were measured from an apical 4-chamber view, as previously described, 21 and atrial volumes were quantified by tracing the atrial endocardial border at endsystole and applying the biplane area-length method. 22 Cardiopulmonary exercise testing was performed in a subgroup of 28 patients according to the modified Bruce protocol.…”
Section: Clinical Investigation Protocolsmentioning
confidence: 99%
“…Because of the heterogeneity of cardiac anatomy, we used a qualitative, subjective assessment of systemic ventricular function from multiview 2-dimensional echocardiography, grading it as normal or mildly, moderately, or severely impaired, 20 while accounting for significant AV valve regurgitation by similarly grading the systemic ventricular end-systolic diameter. Right atrial (RA) and LA length and width were measured from an apical 4-chamber view, as previously described, 21 and atrial volumes were quantified by tracing the atrial endocardial border at endsystole and applying the biplane area-length method. 22 Cardiopulmonary exercise testing was performed in a subgroup of 28 patients according to the modified Bruce protocol.…”
Section: Clinical Investigation Protocolsmentioning
confidence: 99%
“…In that particular study, they also reported that the preoperative oxygen saturation was not a risk factor for postoperative arrhythmia (3). Different from the study by Gewillig et al (3), we investigated the preoperative right atrial pressure rather than the preoperative right atrial size.…”
Section: Discussionmentioning
confidence: 72%
“…While the extracardiac conduit procedure was determined to be a risk factor in the early postoperative period in the study by Kumar et al (1), Chowdhury et al (2) determined bilateral superior vena cava (SVC) and systemic ventricular dysfunction to be risk factors for supraventricular arrhythmia following the extracardiac conduit Fontan operation. In the studies by Gewillig et al (3) and Peters et al (4), advanced age, dilated right atrium, increased preoperative pulmonary artery pressure, increased right atrial pressure, and poor ventricular function were reported to be risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These may lead to severe hypotension by causing an increase in pulmonary venous atrial pressure in a circulation which lacks a right-sided ventricle. The consequence of these arrhythmias and their predisposing factors have been analysed retrospectively by Gewillig et al 8 Eleven patients (10.6%) developed peri- Usually upright including V I *Range in beats 9 rain -1. tRange (mean). ~PR interval varies with heart operative tachycardias which, despite intensive medical treatment, were fatal in ten.…”
Section: Electrocardiogrammentioning
confidence: 99%